A method for energy modeling and simulation implementation of machine tools of selective laser melting. (1st August 2020) - Yi, Li; Glatt, Moritz; Thomas Kuo, Tai-Yen; Ji, Ankyd; Ravani, Bahram; Aurich, Jan C.
Abstract: Additive manufacturing (AM) technologies are providing promising solutions to production of unique parts at reduced material and energy consumptions. However, recent studies show that the sustainable advantage of AM is not always achieved. For ensuring the sustainability of the AM processes, quantification and assessment of the levels of resource consumptions should be carried out at the design phase. To enable the energy prediction and evaluation of AM, this work proposes a method for energy modeling and simulation implementation of AM machines and applies the method to a machine tool of selective laser melting (SLM). Furthermore, the developed simulation approach is validated using an experimental comparison and has been applied in a use case to realize an energy efficiency-oriented AM process design.